2018
DOI: 10.1002/lipd.12043
|View full text |Cite
|
Sign up to set email alerts
|

Indene Compounds Synthetically Derived from Vitamin D Have Selective Antibacterial Action on Helicobacter pylori

Abstract: Helicobacter pylori infects the human stomach and is closely linked with the development of gastric cancer. When detected, this pathogen can be eradicated from the human stomach using wide-spectrum antibiotics. However, year by year, H. pylori strains resistant to the antibacterial action of antibiotics have been increasing. The development of new antibacterial substances effective against drug-resistant H. pylori is urgently required. Our group has recently identified extremely selective bactericidal effects … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
25
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 31 publications
(27 citation statements)
references
References 38 publications
0
25
0
Order By: Relevance
“…Several clinical studies have illustrated that vitamin D analogs may have anti‐ H. pylori antimicrobial effects . Cytological research has also found that vitamin D 3 decomposition product 1 (VDP1) can lyse H. pylori bacterial cells by inducing the collapse of the cell membrane …”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Several clinical studies have illustrated that vitamin D analogs may have anti‐ H. pylori antimicrobial effects . Cytological research has also found that vitamin D 3 decomposition product 1 (VDP1) can lyse H. pylori bacterial cells by inducing the collapse of the cell membrane …”
Section: Introductionmentioning
confidence: 99%
“…[4][5][6][7][8][9][10] Cytological research has also found that vitamin D 3 decomposition product 1 (VDP1) can lyse H. pylori bacterial cells by inducing the collapse of the cell membrane. 11,12 However, the correlation between vitamin D levels and H. pylori has not been fully illustrated, and studies on the impact of serum vitamin D levels on H. pylori eradication were mostly of small sample sizes. Therefore, we conducted a multicenter prospective cohort study with a relatively large sample size to determine whether serum vitamin D levels had an impact on H. pylori infection and eradication, and whether its low level was an independent risk factor affecting H. pylori eradication.…”
Section: Introductionmentioning
confidence: 99%
“…The most important reason may be its antibacterial action against H pylori . Previous study reported that infected macrophages upregulate the production of β‐defensin to kill H pylori strains by VDR . β‐defensins are secreted in the gastric mucosa, playing a pivotal role in the immune response of the gastrointestinal epithelium to H pylori infection .…”
Section: Discussionmentioning
confidence: 99%
“…Several methods have been reported for the preparation of these two biologically active moieties . In addition, indene derivatives have attracted much interest due to their anti‐inflammatory, analgesic, and antibacterial properties . Therefore, the synthesis of compounds having various pharmacophores, such as pyran, quinoxaline, and indole, is very important and they can exhibit unique pharmaceutical properties.…”
Section: Introductionmentioning
confidence: 99%